2019
DOI: 10.1038/s41598-019-54277-w
|View full text |Cite
|
Sign up to set email alerts
|

Access site complications following Impella-supported high-risk percutaneous coronary interventions

Abstract: Mechanical circulatory support (MCS) devices are increasingly used to provide hemodynamic stability for patients with severe coronary artery disease, comorbidities, and/or impaired hemodynamics during high-risk percutaneous coronary interventions (PCI). Vascular access site complications, particularly those due to the use of large-bore sheaths, may limit outcomes in these patients. The aim of this study was to investigate the incidence and predictors of vascular complications in protected high-risk PCIs. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The Impella CP and 5.0/5.5 are widely used microaxial tempMCS devices. The Impella CP is frequently used in protected PCI (percutaneous coronary intervention) and may be a risk modifier if used in acute CS 13,14 . The Impella 5.0/5.5 devices were developed as an alternative to v‐a ECLS for patients with left ventricular failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Impella CP and 5.0/5.5 are widely used microaxial tempMCS devices. The Impella CP is frequently used in protected PCI (percutaneous coronary intervention) and may be a risk modifier if used in acute CS 13,14 . The Impella 5.0/5.5 devices were developed as an alternative to v‐a ECLS for patients with left ventricular failure.…”
Section: Discussionmentioning
confidence: 99%
“…The Impella CP is frequently used in protected PCI (percutaneous coronary intervention) and may be a risk modifier if used in acute CS. 13,14 The Impella 5.0/5.5 devices were developed as an alternative to v-a ECLS for patients with left ventricular failure. Arguments in favor of these devices include a reduced need for anticoagulation and effective LV unloading as well as the possibility of active patient mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to see that the device is being placed properly to avoid possible complications like vascular injury or thrombosis, which may lead to cerebrovascular accident or limb ischemia, bleeding, coagulopathy, and injury to the aortic valve (Mebazaa et al, 2018;Mandawat and Rao, 2017). To lower the rate of vascular complications the angiographic-and fluoroscopic-guided vascular access maybe mandated (Johannsen et al, 2019). There are other complications, as well, which may be taken care of during the process.…”
Section: Complications and Contraindications Of Impellamentioning
confidence: 99%
“…Bleeding complications over time demonstrated that the variability in bleeding risk seen across centres has not changed meaningfully over the last 15 years (Figure 1). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Given the broad scope of bleeding complications (comprising both access and non-access-related bleeding during PCI), often complicated by pre-existing anaemia and the inclusion of some urgent HR-PCI patient populations, this variability is not surprising. Likewise, many series reported relatively low numbers of cases over extended time periods, suggesting that any advantages of increased operator skill, using best practices accrued through increasing experience, could not be ascertained.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%
“…33,34 The rate of vascular complications remained consistently low over time ( Figure 2). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Transfusion rates suggest a downward trend over time (Figure 3). Thus, in the absence of Level 1 evidence and specific guidelines for pVAD support during HR-PCI, variation in approaches further add to the difficulty in analysing overall procedural risk as well as bleeding risk.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%